1996
DOI: 10.1002/(sici)1520-6823(1996)4:1<41::aid-roi7>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Spatially fractionated (GRID) radiation for palliative treatment of advanced cancer

Abstract: SUMMARY To evaluate the use of single large doses spatially fractionated radiation (GRID) therapy either alone or in combination with conventional radiation in the palliative treatment of advanced cancer. Sixty-one patients with advanced cancer who had exhausted conventional approaches to palliative treatment with surgery, chemotherapy and/or radiotherapy were treated with high dose GRID therapy using high energy photons. Seventytwo symptomatic areas of disease were irradiated. A 50:50 GRID (open to closed are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 0 publications
2
58
0
Order By: Relevance
“…Megavoltage GRID radiation therapy is a new paradigm in the management of bulky ͑Ͼ8 cm͒ malignant tumors. [1][2][3][4] The Department of Radiation Medicine at the University of Kentucky has utilized a modified spatially fractionated technique with megavoltage x-ray beam for treatment of advanced tumors. 3,4 Dosimetric characteristics of these GRID radiation fields for both photon and electron beams have been studied by several investigators.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Megavoltage GRID radiation therapy is a new paradigm in the management of bulky ͑Ͼ8 cm͒ malignant tumors. [1][2][3][4] The Department of Radiation Medicine at the University of Kentucky has utilized a modified spatially fractionated technique with megavoltage x-ray beam for treatment of advanced tumors. 3,4 Dosimetric characteristics of these GRID radiation fields for both photon and electron beams have been studied by several investigators.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The Department of Radiation Medicine at the University of Kentucky has utilized a modified spatially fractionated technique with megavoltage x-ray beam for treatment of advanced tumors. 3,4 Dosimetric characteristics of these GRID radiation fields for both photon and electron beams have been studied by several investigators. [5][6][7] It is interesting to know that the published clinical results [1][2][3][4] were obtained with a prototype GRID block that was constructed by placing several segments of copper tubing between two plastic trays and filling the space between the tubes with cerrobend material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Traditional GRID therapy treatments have shown great tumor response of bulky lesions with an overall response rate increase of 62% to 91% when they were treated with a single-dose of GRID therapy (≥15 Gy) followed by conventional extremal beam radiotherapy. 2 Another study of 71 patients with advanced or bulky tumors of varying histologies demonstrated that 78% response rate for pain palliation and 58.5% and 72.5% objective clinical response rate for mass effect after GRID therapy of 10 to 20 Gy dose with or without additional external beam radiation. 3 All these early clinical studies demonstrated no significant skin toxicity with GRID therapy.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of the modern megavoltage energy linear accelerator with skin sparing capabilities, the use of GRID technique gradually disappeared. The GRID technique using megavoltage X-ray was started in the late 1980s (1,2) as a palliative treatment of bulky tumors. Currently GRID therapy is performed either by using a commercially available GRID block (3,4) or multileaf collimator (MLC) (5) of a linear accelerator.…”
Section: Introductionmentioning
confidence: 99%